Promoting Albania's Tourist Attractions: Tourist Guides and Marketing Strategies for the Successful Management of Tour Groups - ULDEDAJ, Gjokë; ORHANI, Edlir (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024DO - 10.14505/jemt.v15.1(73).13, 2024)
Currently, Albania is a growing destination for foreign tourists because the country offers diverse natural, cultural, historical, and spiritual sites. Thanks to the contribution of national and foreign archaeologists, who have shed light on the rich Albanian archaeology, these sites have today received the designation of tourist destinations. However, the current situation does not reflect the full potential of Albania in this field because the country has many more discovered areas that need to be brought to light and promoted. Just as there are, a significant number of historical and cultural objects need to be treated and revived according to the standards of the time. Likewise, there is a need for the tourist guides to find new ways of marketing while leading and guiding the groups of tourists. The purpose of this study is to highlight the problems of promoting tourist attractions and handling cultural objects as well as to suggest new alternatives that are more efficient and compatible with the demands of the time. The methodology used in this research is a combination of qualitative and quantitative methodology. Specifically, for data collection, the main instruments used are a semi-structured interview and a focus group. Also, we have tried to extract data from tourist subjects, the institute of monuments and representatives of the tourism community, through which we have managed to draw conclusions and suggestions. The analysis of the data obtained in this study highlights the urgent need for a new and moderate conception and attitude for the strategy of promoting Albania’s tourist attractions. The Albanian monuments of cultural heritage, as a precious asset, should take a special importance in the life of the country, through the functional promotion that becomes part of the life of its own citizens.